Global Not Local Masker Features Govern the Auditory Continuity Illusion - Riecke, Lars (Society for Neuroscience, 2012)
When an acoustic signal is temporarily interrupted by another sound, it is sometimes heard as continuing through, even when the signal is actually turned off during the interruption—an effect known as the “auditory continuity illusion.” A widespread view is that the illusion can only occur when peripheral neural responses contain no evidence that the signal was interrupted. Here we challenge this view using a combination of psychophysical measures from human listeners and computational simulations with a model of the auditory periphery. The results reveal that the illusion seems to depend more on the overall specific loudness than on the peripheral masking properties of the interrupting sound. This finding indicates that the continuity illusion is determined by the global features, rather than the fine-grained temporal structure, of the interrupting sound, and argues against the view that the illusion arises in the auditory periphery.